Antimicrobial potential of ozone for the storage of grains: special focus on inhibition of bacterial contamination. (14th September 2022) - Singh, Gursharan; Arya, Shailendra Kumar; Bibra, Mohit; Bhalla, Aditya; Aggarwal, Ashish; Singh, Jatinder
Abstract: Ozone (O3 ) is known as the powerful oxidant and has several beneficial applications, especially in biotechnology and agricultural industries. Ozone can be easily created on site with the use of electricity and air. Ozone is a safe antioxidant when used as a substitute to toxic chemical-based pesticides for the storage of grains. As the awareness and preference is augmenting among the people for consumption of organic foods; in this condition, O3 can play the major role as an effective and non-hazardous decontaminant. The O3 has half-life of 20–50 minutes because it rapidly decomposes to diatomic oxygen (O2 ), and leaving no harmful residue on the surface of grains. The, decayed O3 releases a single O2 atom that is highly reactive towards the cell membrane of bacteria and attacks the cellular components and disrupts normal cellular activity. It has been reported that, O3 at 350 to 600 ppm-h can show highly destructive effects on bacterial and fungal vegetative cells. On the other hand, it is also important to optimize the dose of O3 from species to species and genus of the different bacteria. Some strains of Escherichia coli are resistant to the lower dosage of O3 . On overall analysis of scientific opinion and recent outcomes of the laboratory results, we strongly recommend that the use of O3 for the storage of grains should be further investigated and utilized at large scale. Preservation of grains by the use of O3 is also an ecofriendly and considered as a customer-caring method to reduce food pathogens from seed grains without applying any toxic chemicals.